THE FACTORS OF LITIGANTS’ PERCEIVED JUDICIAL BEHAVIOR FAIRNESS - Petkevičiūtė-Barysienė, Dovilė; Valickas, Gintautas (Teisė, 2016)
The article analyzes perceived fairness of judges’ behavior before the start of the trial and after the court process of litigants and its factors: justice expectations, perceived fairness and emotions during the trial, emotions as well as demographic characteristics of litigants.